Habitat prioritization across large landscapes, multiple seasons, and novel areas: An example using greater sage‐grouse in Wyoming. Issue 1 (September 2014) - Fedy, Bradley C.; Doherty, Kevin E.; Aldridge, Cameron L.; O'Donnell, Micheal; Beck, Jeffrey L.; Bedrosian, Bryan; Gummer, David; Holloran, Matthew J.; Johnson, Gregory D.; Kaczor, Nicholas W.; Kirol, Christopher P.; Mandich, Cheryl A.; et al.
ABSTRACT Animal habitat selection is an important and expansive area of research in ecology. In particular, the study of habitat selection is critical in habitat prioritization efforts for species of conservation concern. Landscape planning for species is happening at ever‐increasing extents because of the appreciation for the role of landscape‐scale patterns in species persistence coupled to improved datasets for species and habitats, and the expanding and intensifying footprint of human land uses on the landscape. We present a large‐scale collaborative effort to develop habitat selection models across large landscapes and multiple seasons for prioritizing habitat for a species of conservation concern. Greater sage‐grouse (Centrocercus urophasianus, hereafter sage‐grouse) occur in western semi‐arid landscapes in North America. Range‐wide population declines of this species have been documented, and it is currently considered as "warranted but precluded" from listing under the United States Endangered Species Act. Wyoming is predicted to remain a stronghold for sage‐grouse populations and contains approximately 37% of remaining birds. We compiled location data from 14 unique radiotelemetry studies (data collected 1994–2010) and habitat data from high‐quality, biologically relevant, geographic information system (GIS) layers across Wyoming. We developed habitat selection models for greater sage‐grouse across Wyoming for 3 distinct life stages: 1) nesting, 2) summer, and 3) winter. We developed patch and landscape models across 4 extents, producing statewide and regional (southwest, central, northeast) models for Wyoming. Habitat selection varied among regions and seasons, yet preferred habitat attributes generally matched the extensive literature on sage‐grouse seasonal habitat requirements. Across seasons and regions, birds preferred areas with greater percentage sagebrush cover and avoided paved roads, agriculture, and forested areas. Birds consistently preferred areas with higher precipitation in the summer and avoided rugged terrain in the winter. Selection for sagebrush cover varied regionally with stronger selection in the Northeast region, likely because of limited availability, whereas avoidance of paved roads was fairly consistent across regions. We chose resource selection function (RSF) thresholds for each model set (seasonal × regional combination) that delineated important seasonal habitats for sage‐grouse. Each model set showed good validation and discriminatory capabilities within study‐site boundaries. We applied the nesting‐season models to a novel area not included in model development. The percentage of independent nest locations that fell directly within identified important habitat was not overly impressive in the novel area (49%); however, including a 500‐m buffer around important habitat captured 98% of independent nest locations within the novel area. We also used leks and associated peak male counts as a proxy for nesting habitat outside of the study sites used to develop the models. A 1.5‐km buffer around the important nesting habitat boundaries included 77% of males counted at leks in Wyoming outside of the study sites. Data were not available to quantitatively test the performance of the summer and winter models outside our study sites. The collection of models presented here represents large‐scale resource‐management planning tools that are a significant advancement to previous tools in terms of spatial and temporal resolution. Published 2014. This article is a U.S. Government work and is in the public domain in the USA.